2015
DOI: 10.1155/2015/516895
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Serum IL-33 and sST2 with Breast Cancer

Abstract: Breast cancer is one of the most common malignant diseases in women. The main cause of death from breast cancer is its metastases at distant sites in the body. Interleukin-33 (IL-33) is a cytokine of the IL-1 family and found overexpressed in various cancers. The aim of the present study was to explore the association of serum IL-33 and sST2 with breast cancer. Here, the serum levels of Interleukin-33 (IL-33) and sST2 were found significantly higher in breast cancer patients than in healthy volunteers. Serum l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 21 publications
3
45
0
Order By: Relevance
“…In line with previous findings in other cancers, like myeloproliferative disorders, hepatic cancer, and breast cancer, we found increased serum concentrations of ST2 in MF. Moreover, ST2 concentrations were significantly higher in more advanced stages of MF.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous findings in other cancers, like myeloproliferative disorders, hepatic cancer, and breast cancer, we found increased serum concentrations of ST2 in MF. Moreover, ST2 concentrations were significantly higher in more advanced stages of MF.…”
Section: Discussionsupporting
confidence: 92%
“…In breast cancer patients, serum levels of IL-33 and of its decoy receptor sST2 were enhanced compared to healthy controls. This positively correlated with the expression of vascular endothelial growth factor (VEGF), metalloprotease-11 (MMP-11), or platelet-derived growth factor-C, which are markers of poor prognosis in breast cancer (52). …”
Section: Main Review Textmentioning
confidence: 99%
“…For breast cancer, IL-33 and sST2 may also serve as non-invasive diagnostic marker, as these two proteins are upregulated in the serum of patients [(52) and see also the paragraph on breast cancer above]. However, IL-33 is upregulated in different types of inflammatory diseases (114116) and cancers (111, 112), and this lack of specificity may prevent its use as a biomarker in the daily clinic diagnostic.…”
Section: Main Review Textmentioning
confidence: 99%
“…IL-33 has been found to mediate Th2 immune responses by binding and signaling through ST2L, an orphan receptor in the IL-1R family, to induce NF-κB and MAPK (p38, JNK and ERK1/2) activation, and promote Th2 cytokine production [19][20][21][22][23]. Recent studies have revealed that IL-33 plays a functional role in tumor development, with high levels of serum IL-33 associated with poor prognosis and chemotherapy resistance in various cancers [24][25][26][27][28][29][30]. An IL-33-dependent proliferation response can be induced by the increase and recruitment of type 2 innate lymphoid cells (ILC2s) [31], which produce high levels of IL-13 that consequently promote cholangiocyte hyperplasia [32].…”
Section: Introductionmentioning
confidence: 99%